2022
DOI: 10.1021/acs.jafc.1c08160
|View full text |Cite
|
Sign up to set email alerts
|

Deletion and Overexpression of the AnOTAbzip Gene, a Positive Regulator of Ochratoxin A Biosynthesis in Aspergillus niger

Abstract: The ochratoxin A (OTA) biosynthetic gene cluster includes a bZIP transcription factor (TF) gene (OTAbzip) that has been identified in different fungal species. However, most previous studies identified the OTAbzip gene in ochratoxigenic fungi using bioinformatics methods, while few studies focused on deleting the gene, let alone overexpressing it, to characterize the function of the OTAbZIP TF. Here, we characterized the AnOTAbZIP TF in an ochratoxigenic isolate of Aspergillus niger by deleting and overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Further, the ΔFpf um21 strain was much more susceptible to ROS stress (Figure 7C,D), confirming that FB1 biosynthesis was vital for F. proliferatum in response to oxidative stress. However, a recent study found that the inhibition of OTA biosynthesis results in stronger pathogenicity and ROS tolerance, 9 suggesting the different roles of different mycotoxins biosynthesis in response to ROS stress. Previous research reported that deficiency in fumonisin biosynthesis results in a substantial reduction of F. verticillioides virulence in plant hosts.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the ΔFpf um21 strain was much more susceptible to ROS stress (Figure 7C,D), confirming that FB1 biosynthesis was vital for F. proliferatum in response to oxidative stress. However, a recent study found that the inhibition of OTA biosynthesis results in stronger pathogenicity and ROS tolerance, 9 suggesting the different roles of different mycotoxins biosynthesis in response to ROS stress. Previous research reported that deficiency in fumonisin biosynthesis results in a substantial reduction of F. verticillioides virulence in plant hosts.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In response to pathogen attack, plants establish a broad range of defense responses to protect themselves, including rapid production of reactive oxygen species (ROS). , Importantly, disease development in harvested fruit also results from the disorder of ROS metabolism. , Hence, ROS stress is one of the most important stresses confronted by fungi during the infection process. In turn, ROS detoxification is critical for the pathogenicity of pathogens .…”
Section: Introductionmentioning
confidence: 99%